Intestinal Dysbiosis and Autoimmune Pancreatitis - Yoshikawa, Tomoe; Watanabe, Tomohiro; Kamata, Ken; Hara, Akane; Minaga, Kosuke; Kudo, Masatoshi (Frontiers in Immunology, 2021)
Autoimmune pancreatitis (AIP) is a chronic fibro-inflammatory disorder of the pancreas. Recent clinicopathological analysis revealed that most cases of AIP are pancreatic manifestations of systemic IgG4-related disease (IgG4-RD), a newly established disease characterized by enhanced IgG4 antibody responses and the involvement of multiple organs. Although the immuno-pathogenesis of AIP and IgG4-RD has been poorly defined, we recently showed that activation of plasmacytoid dendritic cells (pDCs) with the ability to produce large amounts of IFN- and IL-33 mediates chronic fibro-inflammatory responses in experimental and human AIP. Moreover, M2 macrophages producing a large amount of IL-33 play pathogenic roles in the development of human IgG4-RD. Interestingly, recent studies including ours provide evidence that compositional alterations of gut microbiota are associated with the development of human AIP and IgG4-RD. In addition, intestinal dysbiosis plays pathological roles in the development of chronic pancreatic inflammation as dysbiosis mediates the activation of pDCs producing IFN- and IL-33, thereby causing experimental AIP. In this Mini Review, we focus on compositional alterations of gut microbiota in AIP and IgG4-RD to clarify the mechanisms by which intestinal dysbiosis contributes to the development of these disorders.